Standards, Agility, and Engineering. - Coallier, François (Computer (00189162), 2007)
The article discusses the impact that standards would have on the information technology (IT) service industry by creating interoperability between businesses and hardware. There are standards used by the International Organization for Standardization (ISO) and the Institute of Electrical and Electronics Engineers (IEEE). It is noted that using an agility-based standpoint for standards development would maintain flexibility in the IT industry. The relationship between engineering standards and software development is discussed, particularly the work of the U.S. National Bureau of Standards and IEEE to set standards.